Czechia: Demography, Family Policy, and Law Instruments to Protect and Support Families - Králíčková, Zdeňka (Demographic Challenges in Central Europe: Legal and Family Policy Response, 2024)
The portrait of the family and family life has been changing in the Czech Republic, particularly over the last five decades, as is reflected in the country’s legal system. Many legislative changes occurred in the Czech Republic after the fall of the Iron Curtain, followed later by others. In this context, the Czech Republic’s accession to several international human rights conventions and the passing of the new Civil Code are relevant. Considering demographic challenges, this chapter focuses on the current Czech family law, in particular, its principles and the instruments aimed at protecting and supporting families, parents, children, and vulnerable family members.Keywords: demography, family law, change, marriage, registered partnership, de facto cohabitation, motherhood, fatherhood, parental responsibility, family solidarity, protection, support, family policy